Condition of macular retina in women at preeclampsia and after the delivery (Ukrainian Journal of Ophthalmology, 2026)
Purpose: An objective assessment of morphometric parameters of a macular retina at preeclampsia.Material and methods. Studying of morphometric parameters of macular retina of 77 pregnant women (154 eyes) with preeclampsia was carried out.Results. The statistically reliable significant rising of macular retina thickness in women in groups with average and serious degree of preeclampsia was taped.Deduction. Most severity retinal changes were created to the 3rd trimester of pregnancy women with serious degree of preeclampsia. In 2–4 months after the delivery the average value of fovea thickness considerably decreased, but still significantly exceeded the primary values; the macular volume of a retina remained raised.Conclusion. It is proved that changes of micromorphometric parameters of retina are directly bound to severity of a preeclampsia. The taped changes of macular retina need to be considered when forecasting risk formation of macular pathology and in many years after the delivery.
Keywords: pregnancy; preeclampsia; optical coherent tomography; macular retina; micromorphometric parameters